DEMOGRAPHIC AND MORPHOLOGICAL CHANGES IN KOLKATA CITY, INDIA DURING 1951-2014 - Pralip Kumar NARZARY; Ambarish Kumar RAI; Shraban SARKAR; Sulochana SHEKHAR; Dinabandhu MAHATA (European Journal of Geography)
Kolkata, one of the oldest cities in India has been the destination for migrants. The influx of population over the time caused demographic and morphological vicissitudes. Hence, the present study aims to analyse the changes in demographic structure, city sprawl, and spatiotemporal changes in land use of Kolkata city during 1951 to 2014. Population data are taken from the Census of India and spatial data from the Landsat satellite image. The geographical area of the city has expanded by more than two folds during 1951-1991.Significant alteration in age-sex structure is noticeable; sex ratio improved from mere 593 to 908, the urban settlement has sprawled from mere 23% to 63% of the city area, whereas the greenery has dwindled to just 2.8%. The most substantial impact of urban sprawl is seen on agricultural/fallow land.